National Adherence to Guidelines for Antimicrobial Prophylaxis for Patients Undergoing Radical Cystectomy. Issue 2 (16th November 2022) - Prunty, Megan; Rhodes, Stephen; Rivero, Marco-Jose; Callegari, Michael; Jesse, Erin; Arenas-Gallo, Camilo; Brant, Aaron; Calaway, Adam; Scherr, Douglas; Shoag, Jonathan E.
Abstract : Purpose: The sentinel reference for antibiotic prophylaxis for radical cystectomy with ileal conduit in the AUA Guidelines reports data from 2003-2013 and has not been updated in the interim. Here, we assess adherence to antibiotic prophylaxis guidelines among patients undergoing radical cystectomy with ileal conduit for bladder cancer using a large national database. As a secondary objective, we assess the association between antimicrobial use and postoperative infection during the index admission following cystectomy. Materials and Methods: The Premier Healthcare Database was queried for all patients undergoing cystectomy with ileal conduit with diagnosis of bladder cancer between 2015 and 2020. Antibiotics used and the duration of use was determined by charge codes and grouped as guidelines-based or not according to 2019 AUA Guidelines. Association with infectious complications was assessed by logistic mixed effects regression models. Results: Among 6, 708 patients undergoing cystectomy with ileal conduit, only 28% (1, 843/6, 708) were given prophylaxis according to AUA guidelines; 1.8% (121/6, 708) of patients received an antifungal and 37% (2, 482/6, 708) received extended duration prophylaxis beyond postoperative day 1. Patients who received guidelines-based prophylaxis were less likely to be diagnosed with a urinary tract infection (21% vs 24%, P = .04), pyelonephritis (5.1% vs 7.7%, P < .001), bacterial infection (24% vs 27%, P = .03), or pneumonia (12% vs 17%, P < .001). There was no statistically significant difference in clostridium difficile infection between guidelines-based and nonguidelines-based prophylaxis (3.2% vs 3.7%, P = .32). In a multivariable logistic regression adjusting for age, race, insurance, and hospital and provider characteristics, nonguideline antibiotic prophylaxis (OR 1.27 [1.12, 1.43], P < .001) was associated with an increased odds of infectious events, whereas a robotic approach (OR 0.82 [0.73, 0.92], P < .001) was associated with lower odds. Conclusions: Seventy-three percent of patients fail to receive guideline-based antibiotic prophylaxis when undergoing radical cystectomy with conduit, which was largely driven by extended duration antibiotic use. Despite the shorter duration of antibiotics, we found that guideline-based prophylaxis was associated with a 25% decrease in the odds of infectious complications. While residual confounding is possible, these data support current AUA guidelines and suggest a need for outreach to improve guideline adherence.